(untitled) (Fiep Bulletin - online, 2014)
This review aims to measure the level of acknowledgment of therapeutic recreation by different professionals working for Santa Cruz Hospital (HSC), as well as report the recreation activities developed at the room placed at HSC’s Pediatrics Unit, that is part of the Child and Teenager Care Project (ACA). Among developed activities are drawing and painting, dovetail games, puzzles, mnemonic games, domino, chess, checkers, playing with dolls, cars and puppets, as well as reading books. The toys, games and books are also lent for in-bed children that cannot go to the recreation room. Aiming identify the level of acknowledgment by other professionals that work at the same hospital, 100 descriptive questionnaires were distributed over all sections of HSC. After three days, data were collected and tabulated. From the answers, we realized that 58.1% of the employees didn’t know about the existence of the space. 93% knew about the function of therapeutic recreation in the hospital, but didn’t know what kind of professional that develops the activities or even notice the existence of the room in the hospital. The employees the met the room considered it as not appropriate for doing the activities. Therefore, there is necessity on intensify the publicity of the work done, because this is considered important and relevant, while helping to improve more happiness and comfort to hospital environment, minimizing the effects of hospitalization on children and their families.